2022
DOI: 10.1155/2022/4247631
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic Segmentation of MRI of Brain Tumor Using Deep Convolutional Network

Abstract: Computer-aided diagnosis and treatment of multimodal magnetic resonance imaging (MRI) brain tumor image segmentation has always been a hot and significant topic in the field of medical image processing. Multimodal MRI brain tumor image segmentation utilizes the characteristics of each modal in the MRI image to segment the entire tumor and tumor core area and enhanced them from normal brain tissues. However, the grayscale similarity between brain tissues in various MRI images is very immense making it difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The research places a particular emphasis on accuracy, sensitivity, specificity, and positive predictive value. The improvement of brain tumor categorization methodology is made possible by this accuracy, which guarantees a targeted and efficient approach [19]- [22].…”
Section: Precision In Problem Formulationmentioning
confidence: 98%
“…The research places a particular emphasis on accuracy, sensitivity, specificity, and positive predictive value. The improvement of brain tumor categorization methodology is made possible by this accuracy, which guarantees a targeted and efficient approach [19]- [22].…”
Section: Precision In Problem Formulationmentioning
confidence: 98%
“…Magnetic resonance imaging (MRI) is one of the most powerful medical diagnostic tools, which has the characteristics of three-dimensional imaging and continuous imaging. It is not only the first choice for imaging the brain and central nervous system, but also the main tool for evaluating the function of heart disease and detecting tumors [ 125 , 126 , 127 ]. Paramagnetic nanoparticles have the advantages of small size, large specific surface area, good suspension stability, and directional transport and enrichment under the effect of an external magnetic field, which shows great potential applications in the biomedical field [ 128 ].…”
Section: Liposome Nanoparticlesmentioning
confidence: 99%
“…Because precise manual segmentation of brain tumors is prohibitively time-consuming, the standard method of assessing for interval change is largely based on a radiologists' gestalt and bi-or triplanar measurements, which can overlook small changes in overall tumor size as well as subtle evolution in tumor heterogeneity and composition over time. Many studies have demonstrated that AI algorithms can match or exceed the segmentation performance of neuroradiologists in a fraction of the time [21][22][23][24][25][26].…”
Section: Segmentation and Preoperative Planningmentioning
confidence: 99%